2021
DOI: 10.3390/cancers13112756
|View full text |Cite
|
Sign up to set email alerts
|

Association of Circadian Clock Gene Expression with Glioma Tumor Microenvironment and Patient Survival

Abstract: Circadian clock genes have been linked to clinical outcomes in cancer, including gliomas. However, these studies have not accounted for established markers that predict the prognosis, including mutations in Isocitrate Dehydrogenase (IDH), which characterize the majority of lower-grade gliomas and secondary high-grade gliomas. To demonstrate the connection between circadian clock genes and glioma outcomes while accounting for the IDH mutational status, we analyzed multiple publicly available gene expression dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 92 publications
(114 reference statements)
0
8
0
Order By: Relevance
“…Upregulation of other genes, such as FREM2 [46], TXNDC12 [38], and the eIF3-complex [11] were only associated with poor prognosis in one cohort per gene, but were not significant in other cohorts. High expression of ADAR3 [44], PER1 [16] and WDFY3-AS2 [42] were associated with improved overall survival in grade 2 and 3 IDHmutant astrocytomas, and for PER1 and WDFY3-AS2 also in grade 4 IDH-mutant astrocytomas. The expression of TGM2 [3] and MPC1 [20] were not associated with overall survival.…”
Section: Gene Expressionmentioning
confidence: 89%
“…Upregulation of other genes, such as FREM2 [46], TXNDC12 [38], and the eIF3-complex [11] were only associated with poor prognosis in one cohort per gene, but were not significant in other cohorts. High expression of ADAR3 [44], PER1 [16] and WDFY3-AS2 [42] were associated with improved overall survival in grade 2 and 3 IDHmutant astrocytomas, and for PER1 and WDFY3-AS2 also in grade 4 IDH-mutant astrocytomas. The expression of TGM2 [3] and MPC1 [20] were not associated with overall survival.…”
Section: Gene Expressionmentioning
confidence: 89%
“…A recent study reported a close association between higher PER expression and better overall survival for IDH-mutated or wild-type samples in TCGA, and PER expression was shown to be an independent prognostic factor in glioma according to a Cox proportional hazards analysis with the glioma microenvironment influencing PER expression. But the level of PER expression obtained from the average of PER1/2/3 expression reflected overall PER expression in the research rather than the level of subgenes [ 25 ]. Previous research indicated that Per2 is highly expressed in low-grade glioma and exhibits low expression in high-grade glioma in clinical samples [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A new study described an inverse correlation between the tumor suppressor activity of CLOCK and hypoxia [49], supporting the thesis that the suppression of CLOCK in tumor cells enhanced survival and reduced migration of the microglia [50]. Future works should increase the acknowledgement of clock genes in glioma research [51].…”
Section: Clock Genementioning
confidence: 65%